Bridging the theory-practice gap - Clapton, Gary; Daly, Maura (Groupwork, 2012)
This paper recounts details of a project designed to enhance integration of student learning for practice, in particular it focuses on placement groupwork with students, evaluates an innovative approach to the use of placement tutors and suggests that there may be more productive ways of using the traditional time spent on placement liaison and visits.